(5x+1)+51=x

Simple and best practice solution for (5x+1)+51=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+1)+51=x equation:


Simplifying
(5x + 1) + 51 = x

Reorder the terms:
(1 + 5x) + 51 = x

Remove parenthesis around (1 + 5x)
1 + 5x + 51 = x

Reorder the terms:
1 + 51 + 5x = x

Combine like terms: 1 + 51 = 52
52 + 5x = x

Solving
52 + 5x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
52 + 5x + -1x = x + -1x

Combine like terms: 5x + -1x = 4x
52 + 4x = x + -1x

Combine like terms: x + -1x = 0
52 + 4x = 0

Add '-52' to each side of the equation.
52 + -52 + 4x = 0 + -52

Combine like terms: 52 + -52 = 0
0 + 4x = 0 + -52
4x = 0 + -52

Combine like terms: 0 + -52 = -52
4x = -52

Divide each side by '4'.
x = -13

Simplifying
x = -13

See similar equations:

| 26+r=2r-2 | | 5x-7=-202 | | 2r+26=4r-2 | | -8(r+9)-7=9 | | xe^(-t)*(dx)/(dt)=t | | 10=3x+-5 | | 250m^3+54= | | m+5=-5m+5 | | (1+4x)+137=x | | 15-1/2b--3 | | 9+-8p= | | x^3-5x^2=4x | | (6x+4)+136=x | | -4x+-2= | | y-2/3=2-y/5 | | 4x-2+4x=4x+9+2x | | X+(n+6)=4n | | 12.06=-4x | | (d^3-6d^2+13d)y=0 | | .6x-5=.2x+7 | | -2(-5x+2)=5(9-2x) | | 4.2=5x | | 5x-8=17.5 | | 5/8x7/12 | | -8=-(m-8) | | X(x+30)=180 | | 1a-1/a^2-9a | | -88=-(m-8) | | -3(5t-5)+6t=8t-9 | | x+2x=x+70 | | 46=-16t^2+46+6 | | -3(-x)= |

Equations solver categories